Program Kemitraan Masyarakat Tentang Penyuluhan Manajemen Bisnis dan Sumber Daya Manusia Serta Pencatatan di Tantri Phala - I Gde Agung Wira Pertama; I Nyoman Sutapa; Ni Luh Putu Mita Miati (Labor Jurusan Sosiologi, Fakultas Ilmu Sosial, Universitas Negeri Padang, 2022)
Tantri Phala is a trading company engaged in the business of trading traditional clothing. The business activities in Tantri Phala, apart from selling merchandise, are also making or producing their own items such as clothes, cloth and shade. Tantri Phala is managed directly by the owner, involving several employees such as employees at the cashier, production and marketing departments. The problems in this Tantri Phala are difficulties in managing the workforce, lack of understanding of accounting, lack of adequate tools for recording. From these problems, the time of service with the Community Partnership Program provides solutions in the form of providing labor management counseling, providing accounting counseling, providing counseling about basic prices. To carry out the implementation, starting from program implementation, evaluation, and partner participation. The targeted outputs are articles published in accredited national journals Abdi Journal: Journal of Community Service and Empowerment Padang State University, print or digital media, intellectual property rights, videos published on websites and books.